Anastomosis of the caudal thoracic duct and intercostal vein using a microvascular anastomotic coupler device: Experimental study in six dogs - Welker, Jamie L.; Hardie, Robert J.; Weber, Katherine A.; Loeber, Samantha J. (Veterinary surgery, 2024)
Objective To describe the technique for anastomosis of the caudal thoracic duct (TD) to the 10th or 11th intercostal vein (ICV) using a microvascular anastomotic coupler (MAC) device in dogs and assess patency of the anastomosis on days 0 and 30. Study design Experimental study. Sample population Six adult Beagle dogs. Methods Under general anesthesia, fluoroscopic popliteal lymphangiography was performed and the TD identified. A right ninth or 10th intercostal thoracotomy was performed. Using an operating microscope, the TD and the 10th or 11th ICV were isolated, ligated, and anastomosed using a 1.5 or 2.0 mm MAC. Fluoroscopic popliteal lymphangiography was repeated immediately after surgery and on day 30. Results The anastomosis was successful and lymphangiography documented flow into the azygos vein in all six dogs immediately after surgery. At day 30, the anastomosis was patent in four of six dogs. In two dogs, flow through the anastomosis was obstructed due to kinking of the ICV just cranial to the MAC. Conclusion Anastomosis of the TD and ICV using a MAC was feasible and was shown to maintain patency up to 30 days. When performing the anastomosis, care should be taken to ensure the ICV is not kinked by the MAC. Clinical significance Direct anastomosis of the TD and ICV may have application for treatment of idiopathic chylothorax in dogs by maintaining flow from the abdominal lymphatics to the central venous circulation and thereby preventing the stimulus for collateral circulation and persistent chylous effusion. Further investigation is warranted to assess the efficacy of this technique in dogs affected with idiopathic chylothorax.